PENYULUHAN TENTANG MANAJEMEN KESEHATAN IKAN PADA BUDIDAYA IKAN HIAS GUPPY (poecilla reticulata) DI ADIPATI FARM, KOTA BANDAR LAMPUNG - Huriyatul Fitriyah Noor; Ciptaning Weargo Jati (Jurnal Media Pengabdian Kepada Masyarakat, 2023)
Fish health is one of main problems faced by fish farmers, one of them is Adipati Farm, an ornamental fish business located in Kedaton, Bandar Lampung City. The occurrence of fish pests and diseases often causes business failure. The lack of knowledge upon quarantine process and good fish health management system is one of the main factors causing fish mortality. The objective of this event was to increase the knowledge about the quarantine process and good fish health management that can help them to increase the succession rate of fish farming process. The method used in this activity is a participatory counseling method with lectures and discussions from the participants. The discussions between resource persons and participants done regarding fish quarantine techniques, fish health management, and the benefits of both applications. The result of this activity is additional knowledge, insight, and awareness of the participants regarding the priority of quarantine and fish health management and their application to support ornamental fish farming businesses. Keywords: Aquaculture, Quarantine Process, Fish Health Management